Antioxidant enzymes expression in seeds and seedlings submitted to stress conditions - Freitas, Aline SIlva (2020)
Population growth and climate change are global realities that put food security at risk. In order to overcome these challenges, breeding programs are investing in the development of highly yield cultivars capable of adapting to different environmental conditions. Proteomic analysis of antioxidant enzymes becomes an important tool for selecting superior genotypes regarding tolerance to abiotic factors. These enzymes are part of an efficient antioxidant system that is able to remove reactive oxygen species, which are produced in cell compartments as a result to different types species that plants can suffer. The present work was performed to study the relationship between antioxidant enzymes and the ability of seeds and seedlings to get tolerance to different types of abiotic stresses. Seeds of rice and corn seeds were submitted or not to water stress while soybean and coffee seed were submitted or not to drying. The following tests were carried out to verify the physiological quality of the seeds: first germination count, germination, accelerated aging, emergence and seedling emergence speed index. Proteomic analyzes were performed on seeds and seedlings from all seeds after the germination test. Expression of SOD, POX, CAT, and APX enzymes were obtained by electrophoresis technique. Western blotting technique was used for accessing the expression of 1-cys-prx enzyme. The activity of the lipid peroxidation, SOD, CAT, and APX enzymes was quantified by spectrophotometry. Proteomic data was submitted to a meta-analysis in order to identify the most efficient protein identification method. The enzymatic analyses pinpointed differences among treatments, which were not identified by the physiological tests. The 1-cys-prx enzyme is an important stress indicator in rice and coffee seeds. Lipoperoxides quantification and antioxidant enzymes are good markers for indicating seed quality loss under stress conditions.